Performance of a Twin-Intake Diesel Engine With Guide Vanes During an Intake Stroke Revealed Through Simulations and Experiments - Hailin Kui (IEEE, 2021)
To improve the flow characteristics of diesel engines with twin intake ports, this study evaluates the installation of guide vanes of varying lengths, heights and angles in front of the intake runner of a CA4DD diesel engine. Considering the interference among various parameters of the guide vane, the parameters were studied with uniform design. To study the effect of guide vanes on the twin-intake diesel engine during the intake stroke, 9 guide vane models, where the vane lengths were 30–70 mm, the vane heights were 1.5-13.5 mm, and the vane angles were 4-36°, were compared with a base model without a guide vane. CATIA was used to build a simulation model, and XFLOW was used to run a three-dimensional (3D) computational fluid dynamics (CFD) simulation. Simulation of different valve lifts of 2–10 mm in steps of 2 mm showed that the guide vane slightly affected the flow coefficient and obviously affected the swirl ratio. Furthermore, designs 4, 5 and 6 had different performance improvements under different valve lifts. The velocity and vorticity of the in-cylinder were evaluated. Moreover, 9 guide vane models were fabricated and tested on a steady-flow test bench. The experimental results show that the swirl ratio average increase of the guide vane models compared to the base model is 21%. The maximum increase is 39% when the guide vane height is 6 mm, the length is 65 mm, and the angle is 24°; when the guide vane height is 7.5 mm, the length is 50 mm, and the angle is 20°, the average increase is 27%. The flow coefficient is less affected and fluctuates at approximately 2%. Hence, the experiments and simulations in this work yield consistent results, and the application of guide vane models compared to a base model can improve the performance of diesel engines.